Present status of capture fisheries in West Kutai regency of East Kalimantan Province, Indonesia - Solihin Iin; Nugroho Thomas; M Wildan Dudi; Sulistiono Sulistiono; Nurussalam Wildan; Effendi Irzal; Hestiriannoto Totok; Edriyan Edriyan; Nurimala Mala; Steven Florensius; Yulian Yulian (BIO Web of Conferences)
The Mahakam River and the Jempang Lake regions are home to the substantial capture fisheries resources in West Kutai Regency. The purpose of this study is to describe the state of the district's capture fisheries. It was carried out in May and August of 2024 in three districts:Muara Pahu, Penyinggahan, and Jempang. The research method used was a descriptive survey by conducting observations and interviews with fishermen. Observations indicate that the three districts have a substantial potential for capture fisheries, with Asian redtail catfish, Indonesian snakehead, pangas catfish, tilapia, and Philippine catfish making up most of the catch. Typically, fishermen employ traditional gear such as lift nets, long lines, net traps, bamboo traps, and gill nets. Non-motorized boats and outboard motorboats make up many fishing vessels. The number of fishermen varies between around 6,822 and 7,508 individuals. One-day fishing is the practice of fishing for a single day, and the annual production of capture fisheries ranges from 1,556 to 1,570 tons. Among the issues faced in the field include the usage of poison, fishing with forbidden gear, and the water level (particularly Jempang Lake) being drastically reduced or even drying up during the dry season.